Field measurements of PM(2.5) infiltration factor and portable air cleaner effectiveness during wildfire episodes in US residences - Xiang, Jianbang (Sci Total Environ, 2021)
Wildfires have frequently occurred in the western United States (US) during the summer and fall seasons in recent years. This study measures the PM(2.5) infiltration factor in seven residences recruited from five dense communities in Seattle, Washington, during a 2020 wildfire episode and evaluates the impacts of HEPA-based portable air cleaner (PAC) use on reducing indoor PM(2.5) levels. All residences with windows closed went through an 18-to-24-hour no filtration session, with five of seven following that period with an 18-to-24-hour filtration session. Auto-mode PACs, which automatically adjust the fan speed based on the surrounding PM(2.5) levels, were used for the filtration session. 10-second resolved indoor PM(2.5) levels were measured in each residence’s living room, while hourly outdoor levels were collected from the nearest governmental air quality monitoring station to each residence. Additionally, a time-activity diary in minute resolution was collected from each household. With the impacts of indoor sources excluded, indoor PM(2.5) mass balance models were developed to estimate the PM(2.5) indoor/outdoor (I/O) ratios, PAC effectiveness, and decay-related parameters. Among the seven residences, the mean infiltration factor ranged from 0.33 (standard deviation [SD]: 0.06) to 0.76 (SD: 0.05). The use of auto-mode PAC led to a 48%−78% decrease of indoor PM(2.5) levels after adjusting for outdoor PM(2.5) levels and indoor sources. The mean (SD) air exchange rates ranged from 0.30 (0.13) h(−1) to 1.41 (3.18) h(−1) while the PM(2.5) deposition rate ranged from 0.10 (0.54) h(−1) to 0.49 (0.47) h(−1). These findings suggest that staying indoors, a common protective measure during wildfire episodes, is insufficient to prevent people’s excess exposure to wildfire smoke, and provides quantitative evidence to support the utilization of auto-mode PACs during wildfire events in the US.